2005
DOI: 10.1038/sj.onc.1208544
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion control of cyclin D1 and p27Kip1 levels is deregulated in melanoma cells through BRAF-MEK-ERK signaling

Abstract: Mutations in BRAF, a component of extracellular signalregulated kinases 1 and 2 (ERK) cascade, are frequent in melanoma. It is important to understand how BRAF mutations contribute to malignant traits including anchorage-and growth factor-independence. We have previously shown that efficient activation of ERK in normal human epidermal melanocytes (NHEM) requires both adhesion to the extracellular matrix and growth factors. Mutant V599E BRAF is sufficient to promote ERK activation independent of adhesion and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 61 publications
8
130
2
Order By: Relevance
“…Initially, we show that mutant B-RAF expression is required for cyclin D1 expression and p27 Kip1 downregulation in melanoma cells. These data complement our previous studies showing that expression of mutant B-RAF is sufficient to upregulate cyclin D1 and downregulate p27 Kip1 in human melanocytes, and that pharmacological inhibition of the B-RAF effector, MEK, has the opposite effects in melanoma cells (Bhatt et al, 2005). Our findings also provide mechanistic details that underlie others' studies in melanoma cells showing that B-RAF-MEK signaling is necessary for S-phase entry, proliferation and anchorage-independent growth in vitro (Collisson et al, 2003;Hingorani et al, 2003;Karasarides et al, 2004;Sumimoto et al, 2004), and growth in vivo (Collisson et al, 2003;Sumimoto et al, 2004;Sharma et al, 2005), and the report that B-RAF V600E transforms mouse melanocytes (Wellbrock et al, 2004b).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Initially, we show that mutant B-RAF expression is required for cyclin D1 expression and p27 Kip1 downregulation in melanoma cells. These data complement our previous studies showing that expression of mutant B-RAF is sufficient to upregulate cyclin D1 and downregulate p27 Kip1 in human melanocytes, and that pharmacological inhibition of the B-RAF effector, MEK, has the opposite effects in melanoma cells (Bhatt et al, 2005). Our findings also provide mechanistic details that underlie others' studies in melanoma cells showing that B-RAF-MEK signaling is necessary for S-phase entry, proliferation and anchorage-independent growth in vitro (Collisson et al, 2003;Hingorani et al, 2003;Karasarides et al, 2004;Sumimoto et al, 2004), and growth in vivo (Collisson et al, 2003;Sumimoto et al, 2004;Sharma et al, 2005), and the report that B-RAF V600E transforms mouse melanocytes (Wellbrock et al, 2004b).…”
Section: Discussionsupporting
confidence: 89%
“…Two Skp2 immunoreactive bands were observed consistent with others' reports Sutterluty et al, 1999;Garriga et al, 2003). We have previously shown that serum-starved NHEM express high levels of p27 Kip1 that are downregulated in an adhesion and growth factor-dependent manner (Bhatt et al, 2005). We next determined whether Skp2 levels were regulated by adhesion and/or growth factors in NHEM.…”
Section: Skp2 Expression Is Enhanced In Melanoma Cells and Downregulasupporting
confidence: 88%
See 3 more Smart Citations